Rape : Some etiological factors and the need to reform the law / Mohd. Marzuki Ibrahim - Ibrahim, Mohd. Marzuki (Faculty of Law, 1985)
To a woman the definition of rape is a fairly simple one. It is meant by a sexual invasion of the body by force, an incursion into the private, personal inner space without consent - in short, an internal assault from one of several avenues and by one of several methods - constitutes a deliberate violation of emotional, physical and rational intergrity and is a hostile, degrading act of violence. And yet by tracing man's concept of rape as he defined it in his earliest laws, we now know with certainty that the criminal act he viewed with horror, and the deadly punishments he saw fit to apply, had little to do with an actual act of sexual violence that a woman's body might sustain. But the law has come some distance from ; such meaning, since the beginning of that earliest laws.